2015
DOI: 10.1556/aalim.2014.0013
|View full text |Cite
|
Sign up to set email alerts
|

Basic nutritional properties of cornelian cherry (Cornus masL.) cultivars grown in the Czech Republic

Abstract: The ascorbic acid, total polyphenols, total anthocyanins and mineral content, together with antioxidant activity, was determined in fi ve Czech, two Ukrainian and two Austrian cultivars of cornelian cherry (Cornus mas L.) widely grown in the Czech Republic. Ascorbic acid content varied between 199-433 mg kg -1 , total polyphenols between 2174-6143 mg kg -1 , and total anthocyanins between 61-253 mg kg -1 . All fruits were good sources of major metals (K, Ca, Mg, Fe, and Mn) and trace elements (Cu, Zn, and Cr).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
7
8
1
Order By: Relevance
“…The obtained results for C. mas were within the limits of the TPC values of C. mas published by several authors from Greece, the Czech Republic, Poland, Romania, Azerbaijan, and Turkey [ 3 , 6 , 26 , 28 , 73 ]. Rop et al [ 77 ] stated that the total amount of polyphenols content was cultivar dependent.…”
Section: Resultssupporting
confidence: 85%
“…The obtained results for C. mas were within the limits of the TPC values of C. mas published by several authors from Greece, the Czech Republic, Poland, Romania, Azerbaijan, and Turkey [ 3 , 6 , 26 , 28 , 73 ]. Rop et al [ 77 ] stated that the total amount of polyphenols content was cultivar dependent.…”
Section: Resultssupporting
confidence: 85%
“…Moreover, this table also shows the percentage of the dietary reference intake values (DRI%) taken for the body by assessing the results of our study in case an adult consumes 1 kg of Cornelian cherries per day. (18). When the present data was compared to the Cetkovska et al (2015) study, though the Ca and K concentrations were lower, Fe concentration were higher than the specified interval they identified.…”
Section: Resultssupporting
confidence: 38%
“…The findings of the study demonstrated that the mineral components and antioxidant activity of the Cornelian cherry were consistent with the studies presented in literature. As already reported in the literature slight differences can be attributed to several reasons; climatic factors, soil type, geographical and environmental conditions, degree of fruit ripeness, manipulation during fruit processing, and selection of analytical methods (18). Moreover, the differences in results for antioxidant property of this fruit can be caused by the solvent type.…”
Section: Resultsmentioning
confidence: 75%
“…Our research showed that TPC and DPPH are dependent, but weakly correlated, what leads to the final statement that DPPH scavenging is not solely caused by molecules active against Folin-Ciocalteau's reagent. Furthermore, Cetkovská et al (2015) measured DPPH scavenging with the use of different analytical technique, i.e. electron paramagnetic spectroscopy, which makes our results not fully comparable.…”
Section: Discussionmentioning
confidence: 92%